Incomplete pass-through and variability in domestic prices: empirical evidence from the Indian wheat market - Ashutosh K. Tripathi; Ashok K. Mishra (Agricultural and Resource Economics Review)
The study estimates the contribution of changes in world prices, exchange rates, and trade policies in explaining the variability of domestic prices under the scenario of incomplete transmission of changes and a counterfactual scenario of complete pass-through. We utilize data from the Indian wheat market for the period 2006–09 and 2017–20. The findings reveal an improvement in the pass-through of changes from the landed price to domestic markets. The price transmission elasticity increased from 50% in 2006/07–2008/09 to 67% during 2017/18–2019/20. The policy response to rising (declining) global prices of decreasing (increasing) import tariffs had a significant effect on prices. The variation in exchange rate offsets the impact of declining or rising global prices on domestic prices.